2008
DOI: 10.1021/ac071475c
|View full text |Cite
|
Sign up to set email alerts
|

IR Laser Extraction Technique Applied to Oxygen Isotope Analysis of Small Biogenic Silica Samples

Abstract: An IR-laser fluorination technique is reported here for analyzing the oxygen isotope composition (delta18O) of microscopic biogenic silica grains (phytoliths and diatoms). Performed after a controlled isotopic exchanged (CIE) procedure, the laser fluorination technique that allows one to visually check the success of the fluorination reaction is faster than the conventional fluorination technique and allows analyzing delta18O of small to minute samples (1.6-0.3 mg) as required for high-resolution paleoenvironm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 39 publications
2
65
1
Order By: Relevance
“…It has been shown that up to a temperature of 70 • C the extraction has no effect on the δ 18 O (Crespin et al, 2008). We verified that it did not have any effect on the 17 O-excess either, using our internal standard MSG extracted at 60 and 70 • C (Crespin et al, 2008). The obtained 17 O-excess values were similar (−211 and −243 per meg, respectively) given our reproducibility of ±34 per meg (see Sect.…”
Section: Phytolith Chemical Extractionssupporting
confidence: 75%
See 2 more Smart Citations
“…It has been shown that up to a temperature of 70 • C the extraction has no effect on the δ 18 O (Crespin et al, 2008). We verified that it did not have any effect on the 17 O-excess either, using our internal standard MSG extracted at 60 and 70 • C (Crespin et al, 2008). The obtained 17 O-excess values were similar (−211 and −243 per meg, respectively) given our reproducibility of ±34 per meg (see Sect.…”
Section: Phytolith Chemical Extractionssupporting
confidence: 75%
“…Phytoliths from soils were extracted following Crespin et al (2008) using HCl, H 2 O 2 , C 6 H 5 Na 3 O 7 and Na 2 O 4 S3-H 2 O at 70 • C, and a ZnBr 2 heavy liquid separation. It has been shown that up to a temperature of 70 • C the extraction has no effect on the δ 18 O (Crespin et al, 2008).…”
Section: Phytolith Chemical Extractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To remove these and other contaminants from diatom samples, a number of chemical and physical clean-up methodologies have been used (e.g. JuilletLeclerc, 1986;Shemesh et al, 1988;Shemesh et al, 1995;Singer and Shemesh, 1995;Morley et al, 2004;Rings et al, 2004;Swann et al, 2006;Tyler et al, 2007;Crespin et al, 2008). The success of the purification process is controlled by factors such as: (a) the ability of chemical reagents to fully oxidize certain components (e.g.…”
Section: Concentration and Purificationmentioning
confidence: 99%
“…Under CIE, oxygen in the -Si-OH layer of the diatom is exchanged with water containing a known δ 18 O ratio (Labeyrie and Juillet, 1982;Juillet-Leclerc and Labeyrie, 1987;Crespin et al, 2008).…”
Section: Oxygen Isotopesmentioning
confidence: 99%